The Effect of Liquidity, Leverage, and Total Asset Turnover on Company Profitability in the Jakarta Islamic Index 70 - Nabila Intan Azzah; Suryo Budi Santoso; Sri Wahyuni; Ani Kusbandiyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Data obtained from the Indonesia Stock Exchange (IDX) shows an increase in the number of investors in the last five years. However, the market capitalization of the Jakarta Islamic Index (JII) has decreased. The company's financial performance is one of the main indicators in evaluating the health and sustainability of the company's operations. In this context, liquidity, leverage, and total asset turnover are important elements that play a significant role in influencing the level of company profitability. This study aims to analyze the influence between these three variables and the company's profitability. The population in this study are companies listed on the Jakarta Islamic Index 70 for the period 2021-2023. Sampling used purposive sampling technique and resulted in a sample of 182 companies that met the criteria. Multiple linear regression was used as the data analysis method. The results showed that liquidity and leverage have no effect on profitability. While total asset turnover has a positive effect on profitability. This study uses the object of the Jakarta Islamic Index 70 which is the most recent Islamic stock index on the IDX compared to the JII and ISSI. The results of this study provide important implications for company management, including reevaluating the use of leverage, efficient use of assets, strategies for liquidity to increase profitability and maintain investment confidence in the Islamic stock market.